Association between acromioclavicular joint pain and capsular bulging in adolescent baseball players - Hatta, Taku; Yamamoto, Nobuyuki; Sano, Hirotaka; Nagamoto, Hideaki; Kurokawa, Daisuke; Takahashi, Hiroyuki; Tanaka, Minoru; Koike, Yoichi; Itoi, Eiji (Knee Surgery, Sports Traumatology, Arthroscopy, 2016)
Purpose The purpose of this study was to investigate the association between acromioclavicular (AC) joint pain and superior capsular bulging assessed by ultrasound in adolescent baseball players. Methods One hundred and fifty players (1st–8th graders) were examined. All subjects underwent physical examinations, including assessment of tenderness on the AC joint and provocative tests (the Buchberger’s test and the cross-body adduction stress test). Bilateral AC joints with the arm in both the resting and the cross-body positions were examined by ultrasound. Results Twelve of 150 players (8 %) had AC symptoms with both positive tenderness and positive provocative tests. Interestingly, their prevalence increased with age—one of the 70 (1.4 %) 1st–3rd graders, six of 46 (13 %) 4th–6th graders and five of 34 (15 %) 7th–8th graders. Ultrasonography of AC joints in the cross-body position showed that the difference in superior capsular bulging between the throwing and non-throwing sides was significantly greater in symptomatic players (1.6 ± 1.2 mm) than in asymptomatic players (0.2 ± 0.8 mm) ( p = 0.002). Conclusion The prevalence of superior capsular bulging was significantly higher in adolescent baseball players with AC joint pain than in those without it. In adolescent baseball players with shoulder pain, AC joint symptoms should be considered amongst potential causes. Careful observation of these patients is suggested in cases of superior capsular bulging of the AC joint as determined by ultrasonography. Level of evidence III.